2008
DOI: 10.1021/ol800925v
|View full text |Cite
|
Sign up to set email alerts
|

Homoallyllic Nitrone Isomerization: Convenient Enantioselective Synthesis of Homoallylic Nitrones and Homoallylic Hydroxylamines

Abstract: An alpha-regioselective synthesis of homoallylic nitrones from aldehydes is reported on the basis of [3,3]-sigmatropic rearrangement. The products are obtained in up to 99% enantioselectivity and up to 80% yield under environmentally benign and mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the particular case of a-N-homoallylamino nitriles, a subsequent aza-Cope rearrangement takes place to afford previously unreported (2-azoniaallyl)zinc intermediates, [50] which lead to 2,3-methanopyrrolidines after a [3 + 2] cycloaddition process. Remarkable features of this mechanism include a chirality transfer through an asymmetric aza-Cope rearrangement, which is rather uncommon, [51] and the formation of a metalated azomethine-ylide that is configurationally stable on the timescale of the subsequent reaction. Additional mechanistic studies are underway in our group to fully understand the [3 + 2] process and will be reported in due course.…”
Section: Resultsmentioning
confidence: 99%
“…In the particular case of a-N-homoallylamino nitriles, a subsequent aza-Cope rearrangement takes place to afford previously unreported (2-azoniaallyl)zinc intermediates, [50] which lead to 2,3-methanopyrrolidines after a [3 + 2] cycloaddition process. Remarkable features of this mechanism include a chirality transfer through an asymmetric aza-Cope rearrangement, which is rather uncommon, [51] and the formation of a metalated azomethine-ylide that is configurationally stable on the timescale of the subsequent reaction. Additional mechanistic studies are underway in our group to fully understand the [3 + 2] process and will be reported in due course.…”
Section: Resultsmentioning
confidence: 99%
“…Wuts and Jung reported the 2‐aza‐Cope rearrangement of nitrones under catalysis with trimethylsilyl triflate,16 which actually involves hydroxyiminium cations. A similar process was described twenty years later by Loh and co‐workers using 10‐camphorsulfonic acid (CSA) as a catalyst 17. In both cases, the rearrangement involved cationic species, as in other 2‐aza‐Cope rearrangements.…”
Section: Introductionmentioning
confidence: 71%
“…84 Homoallylic nitrones are prepared from homoallylic hydroxylamines and aldehydes upon treatment with (+)-10-camphorsulfonic acid (CSA) catalyst via the 2-oxonia- [3,3]-sigmatropic rearrangement regioselectively (eq 16). 85 N-Vinylnitrones have been prepared by a two-step method; the reactions of αchloroaldehyde or α-phenoxyor α-acetoxyketone with Nbenzylhydroxylamines followed by treatment with a base (eq 17). 86 Oxazoline N-oxides (eq 18) 87 and imidazoline N-oxides 88 are obtained by condensations of heteroatom-substituted hydroxylamines with orthoesters.…”
Section: Oxidation Reactionmentioning
confidence: 99%